Genetic transformation of Hevea brasiliensis Muell. Arg. using intact explants as target tissues for Agrobacterium infection - Kala R G; Jayashree R; Reshmi J; Sobha S; Thulaseedharan A (Journal of Tropical Agriculture, 2014)
Genetic transformation is a promising tool for the improvement of the natural rubber producing tree, Hevea brasiliensis, through the incorporation of agronomically important genes. Agrobacterium mediated genetic transformation and regeneration of transgenic plants in H. brasiliensis was previously achieved using callus as the target tissue. The present study proves the feasibility of using intact explants directly as target tissue for Agrobacterium infection. Three target tissues, viz, leaf explants from glass house and pre-cultured in modified MS medium for one week, and leaf and root explants from in vitro developed somatic plants were used in the study. A tumefaciens harbouring the binary vector carrying superoxide dismutase (MnSOD) gene for abiotic stress tolerance, GUS as reporter gene and npt II gene for antibiotic selection was used. Different explant pretreatments such as air drying in laminar air flow hood, soaking in sterile water, sterile water containing acetosyringone (40 mgl-1) and sterile water containing acetosyringone (40 mgl-1) and picloram (2.0 mgl-1) for 20 minutes were given prior to infection with Agrobacterium. Both precultured leaf and in vitro root explants soaked in sterile water containing acetosyringone (40 mg l-1) and picloram (2.0 mg l-1) responded well to bacterial infection with in vitro root explants giving maximum transformation efficiency (67 per cent). The optimum concentration of kanamycin required for selection of infected explants was 50 mg l-1 and callus induction was obtained from the infected explants after three weeks. Newly formed callus from infected root explants were proliferated and the GUS histochemical assay was positive. The genomic DNA isolated from randomly selected putatively transgenic callus lines were subjected to PCR analysis with GUS, npt II and MnSOD gene specific primers. Gene amplification was obtained using GUS (650 bp), npt II (800 bp) and MnSOD (700 bp) gene specific primers.
Source Year: 2014
Keywords: Agrobacterium; GM; Intact explant; MnSOD; Transformation; Transgenic